Growth performance, nutrient digestibility and production economics of fattener pigs supplemented with graded level of indigenously developed pig specific mineral mixture - SINGH, UDEYBIR; SHARMA, AMIT; SINGH, ASHWANI KUMAR; SETHI, A P S (The Indian Journal of Animal Sciences, 2021)
Present study was conducted to evaluate the effects of supplementation of pig specific mineral mixture on growth performance, nutrient digestibility and production economics. Fattening pigs (12) of 4 month-old, with an average body weight of 47.12±0.13 kg were subjected to 3 different isocaloric and isonitrogenous rations having pig specific mineral mixture at the rate of 0, 1.5 and 2.0%, respectively. Growth performance and digestibility coefficient of nutrients were assessed at 45 days and 90 days of experiment. Results showed that during the entire experimental periods pig specific mineral mixture supplementation @ 1.5% significantly improved body weight gain, FCR of pigs over control but further no significant improvement was observed with 2% supplementation rate. However, in comparison to control, only at 90th days of experiment digestibility coefficient of DM, CP and EE was significantly higher in pigs supplemented with 1.5% mineral mixture with no significant difference with 2% supplemented group. Moreover, calcium retention at both 45th and 90th day and phosphorus retention only at 90th days of experiment was significantly better in pigs supplemented with 1.5% mineral mixture with no further improvement with 2% supplementation. Margin of receipts per pig over feeding cost in 1.5% supplemented group was highest and was Rs. 833.60 higher than control. It was concluded that dietary inclusion of pig specific mineral mixture @ 1.5% is sufficient to improve the growth performance and nutrient digestibility with highest economic return from fattener pigs.